Подарок любимой Коллекция поэзии и живописи - Н. Я. Агнивцев; И. Ф. Анненский; Е. А. Баратынский; К. Н. Батюшков; А. А. Блок; В. А. Брюсов; М. А. Волошин; Н. С. Гумилев; Д. В. Давыдов; С. А. Есенин; В. А. Жуковский; Н. А. Клюев; et al. (Москва, Белый город, 2011)
Книга находится в премиум-версии платформы «Русский как иностранный».